Pembuatan Aplikasi Sistem Informasi Akuntansi pada Toko Bahan Kue di Denpasar - Paula Ayu Astelia; Alexander Setiawan; Silvia Rostianingsih (Jurnal Infra, 2016)
Cake grocery store in Denpasar is a business which sells ingredients and tools for baking such as eggs, flour, sugar, butter, baking, oven, and so on. In running the business, mostly grocery stores depend on human to control the business progress. It frequently causes human error risks. Besides, manual system is still used to create the report.Based on the explained backgrounds above, accounting information system has been designed to computerize business process and improve business process control in cake grocery store in Denpasar. That system was build using Microsoft Visual Studio 2010 and MySQL as database. The result obtained that the system is successfully used to collect master records for suppliers, item categories, item and COA, and general ledger. Moreover, the records of transactions, e.g. purchase and sales, as well as the financial statements, e.g. income statement, balance sheet, statement of owner’s equity, purchase report, sales report, and balance sheet.Overall the application in accordance with cake grocery store in Denpasar requirements. From the results of questionnaires conducted that 100% of users agree that the design of the program is good, the completeness of the information needed is good, 60% of users agree that the accuracy of the information and data is good, 80% of users agree about the benefits of the application is good.